STUDIES OF BOSWELLIA OVALIFOLIOLATA BAL. AND HENRY-AN ENDEMIC AND ENDANGERED MEDICINAL PLANT - N. SAVITHRAMMA; P. VENKATESWARLU; D.SUHRULATHA; S.K.M. BASHA; CH. VENKATA RAMANA DEVI (The Bioscan, 2010)
Boswellia ovalifoliolata Bal. & Henry is narrow endemic tree taxa on Tirumala hills of Eastern Ghats. The leaves, bark and gum which are highly medicated. The taxa are used by tribal and indigenous community to treat number of ailments. The studies revealed that the Boswellia ovalifoliolata synthesis a variety of secondary metabolites; and the gum and stem bark showed variation in the accumulation of individual amino acids, lipids, anthocyanins, phenols and flavonoids. Very little systematic and scientific investigations are available on the ethno-medico-botanical claims. Hence the present study was carried out on Boswellia ovalifoliolata as the basic source for the production of pharmaceutical drugs.